Changes in zebra finch central nervous system morphology associated with developmental cannabinoid exposure - Gilbert, Marcoita Terreen (East Carolina University, 2012)
Adolescent CNS development is a highly organized, coordinated process that is both genetically and environmentally influenced, and is characterized by a period of dynamic, activity-dependent changes in synaptic connectivity. Growing evidence suggests that adolescent cannabis use is a risk factor for the development of persistent alterations in brain function. Taeniopygia guttata, the zebra finch, was used as a model of cannabinoid-altered vocal learning. We explored effects of cannabinoid-altered signaling during normal late-postnatal CNS development, as well as lasting morphological changes following exogenous cannabinoid exposure. In these studies, the cannabinoid agonist WIN 55,212-2 was administered to developing male zebra finches during sensorimotor song learning and dendritic spine densities measured following Golgi-Cox impregnation. Within HVC, a region necessary for songbird vocal production, and Area X, a striatal region essential for song learning, dendritic spines were inappropriately elevated by an average of 25% following developmental cannabinoid treatment. Treatments of adults that had already learned song were not associated with spine density changes. Cannabinoid-altered song and neuronal morphology were correlated with changes in levels of proteins related to cell signaling and morphology, including axonal Nf-200 and dendritic MAP2. After sensorimotor developmental cannabinoid treatment, anti-Nf-200 and -MAP2 antibodies were used to immunohistochemically confirm Golgi-Cox staining results. In the same brain areas where dendritic spines were elevated following CB agonist treatment, Nf-200 and MAP2 immunoreactivity (ir) were also elevated. To investigate mechanisms of cannabinoid-induced changes in neuronal morphology, we measured expression of the cytoskeletal protein Arc in NCM. A single exposure to novel song increased the postsynaptic densities of Arc protein. Two exposures to song were sufficient to produce habituation of this response. Habituation was prevented by pretreatment with WIN. These findings suggest there is a persistent, developmentally-restricted condition during periadolescence, and that cannabinoid agonism interferes with sensory integration and encoding necessary for accurate formation of memories.
Keywords: Neuroscience; Pharmacology; Cannabinoids; Dendritic spines; Learning; Memory; Song system; Zebra finches; Biology, Neuroscience; Neuropharmacology; Central Nervous System; Cannabis--adverse effects; Cannabis--chemistry; Finches; Win 55212-2; Learning--physiology; Memory--physiology; Adolescent Development--drug effects; Models, Animal; Vocalization, Animal--physiology; Singing--drug effects; Gene Expression--physiology